Sosialisasi Bahaya Penggunaan Media Sosial Pada Siswa SMPN 09 Pangkalpinang - yuriko, syilva qonita; Carissa, Fihan; Saputra, Davin Eza; Fauzan, Muhammmad; Maulana, Sandi; Zaliman, Iski (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
The use of social media among children and adolescents has been increasing lately. This can certainly have negative impacts on their development, such as addiction, the spread of personal information, cyberbullying, and content that is not appropriate for their age. Therefore, efforts are needed to socialize children and parents about the dangers of unwise use of social media. This socialization activity aims to increase the understanding of the participants, both children and parents, about the risks and negative impacts of excessive and uncontrolled use of social media. The material presented covers the introduction of types of social media, their features, and the potential dangers that can be caused, such as the spread of personal information, cyberbullying, exposure to negative content, and addiction. This activity is carried out through presentations, discussions, and question and answer sessions. Evaluation is carried out to measure the level of understanding of the participants before and after the activity. The evaluation results show a significant increase in the understanding of the participants after participating in this socialization. It is hoped that the knowledge gained can help children and parents use social media more wisely and safely